2008
DOI: 10.1063/1.2838350
|View full text |Cite
|
Sign up to set email alerts
|

Control of resistance switching voltages in rectifying Pt∕TiOx∕Pt trilayer

Abstract: The Pt∕TiOx∕Pt trilayer with electrically asymmetrical interface have been synthesized by means of the reactive sputtering technique followed by the oxygen annealing. The initial current-voltage characteristics in the Pt∕TiOx∕Pt trilayer cell have rectifying behavior originated from the Schottky junction formed between TiOx and Pt top electrode layer. The series connection of Pt∕TiOx∕Pt trilayer cells brings about the control of the reset and set voltages depending on the resistance of the connected Schottky d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 10 publications
1
38
0
1
Order By: Relevance
“…But the exact natures of the filaments and the actual mechanism have not been clearly elucidated. In the modern researches, many TiO 2 films are reported being deposited by reactive sputtering or by atom layer deposition (ALD) on conductive substrates to fabricated MIM structures [7][8][9]. Recently, it is reported that TiO 2 thin films can be easily formed by the thermal oxidation of TiN or Ti layers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…But the exact natures of the filaments and the actual mechanism have not been clearly elucidated. In the modern researches, many TiO 2 films are reported being deposited by reactive sputtering or by atom layer deposition (ALD) on conductive substrates to fabricated MIM structures [7][8][9]. Recently, it is reported that TiO 2 thin films can be easily formed by the thermal oxidation of TiN or Ti layers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Metal/oxide Schottky diodes can also work as memory select devices [32][33][34][35][36][37]. In a TiO x -based diode with (In,Sn) 2 O 3 (ITO) and Pt as electrodes, temperature-dependent current-voltage (I-V) characteristics confirms that Schottky barrier of ∼0.55 eV forms at the TiO x /Pt interface [32].…”
Section: Metal/oxide Schottky Diodesmentioning
confidence: 86%
“…A rectifying Ti/TiO 2 /Pt diode was found to transition into a resistive switching device after a strong forming process, which is attributed to the destruction of the interface Schottky barrier by conductive filaments [36]. Similarly, a Pt/TiO x /Pt was also shown to behave as a switchable rectifier [37,38]. The coexistence of rectifying and switching behaviors in oxide diodes manifests the complexity of these material systems, which may cause reliability concerns.…”
Section: Metal/oxide Schottky Diodesmentioning
confidence: 99%
“…As an antifuse, the fresh device can be set to a low resistance state and kept in LRS permanently with a rectification ratio exceeding 10 4 . As is shown in Figure 8, the memory devices exhibit a large ON/OFF ratio of about 10 6 , narrow resistance Table 1 Partially reported rectifying diodes for 1D1R application Diode type Diode structure Current density F / R ratio Fabrication temperature p-Si/n-Si [18] > 10 5 A/cm 2 >10 5 @1 V >1000°C Si-based diodes Al/p-Si [19] -10 4 @2.3 V -p-NiO x /n-TiO x [14] 5×10 3 A/cm 2 @3 V 10 5 @±3 V <300°C p-CuO x /n-InZnO x [16] 3.5×10 4 A/cm 2 @2.45 V 10 6 @±2.45 V Room temperature Oxide-based diodes (p-n junction type) p-NiO x /n-ITO x [28] > 10 4 A/cm 2 @1.5 V <10 3 Ambient temperature (In,Sn) 2 O 3 /TiO 2 /Pt [15] 400 A/cm 2 @1 V 1.6×10 4 @±1 V 250°C Pt/TiO x /Pt [21] 50 A/cm 2 @-1 V 10 3 @ ±1 V 200°C Oxide-based diodes (schottky type) Ag/ZnO/Ti/Au [22] 10 4 A/cm 2 >10 7 100°C…”
Section: Self-rectifying 1r Structure In Rram Passive Crossbar Arraymentioning
confidence: 99%
“…Nevertheless, these three basic requirements are difficult to be satisfied simultaneously in one Zener diode to match the performance of RRAM cell, which presents difficulties for the development of 1D1R structure based on bipolar RRAM [17]. Considering the different materials used in the diodes, the types of diodes employed in the 1D1R structure mainly include Si-based diode [18,19], oxide-based diode [16,[20][21][22] and polymer-based diode [23,24]. Cho et al [19] have fabricated the Schottky-type Al/p-Si diode with a rectification ratio as high as 10 4 at ±2.3 V (as shown in Figure 7(a)).…”
Section: Rectifying Diode-based 1d1r Structure In Rram Passive Crossbmentioning
confidence: 99%